Studies on phytoplankton productivity in Kavaratti Atoll, Lakshadweep - Suresh, V R; Mathew, K J (Indian Journal of Fisheries, 2011)
Productivity contribution of phytoplankton in Kavaratti Atoll, Lakshadweep, was studied for one year (Jan, to Dec, 1989) using light and dark bottle method. Gross production (mg C/m%r) varied between 0.62±0.01 and 6.0±2.5 and net production between 0.2±0.13 and 1.46±0.85. Gross production showed seasonal variations with a fall during monsoon months (June-September). Productivity appeared highly variable and limited by salinity as well as light conditions.